The doubt factory : a novel - Bacigalupi, Paolo (New York : Little, Brown and Company, 2014)
"When a radical band of teen activists claim that Alix's powerful father covers up wrongdoing by corporations that knowingly allow innocent victims to die in order to make enormous profits from unsafe products, she must decide if she will blow the whistle on his misdeeds"--
English language and literature.
Keywords: Whistle blowing -- Fiction; Fathers and daughters -- Fiction; Corporations -- Corrupt practices -- Fiction; Social action -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Law & Crime; JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Family / Alternative Family; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance.